MENGEMBANGKAN POTENSI KARANG TARUNA MELALUI OPTIMALISASI ORGANISASI BIDANG KEUANGAN DAN BISNIS SEBAGAI UPAYA MENINGKATKAN PERAN PEMUDA DI MASYARAKAT - Dira Karlina; Ryan Elfahmi; Reza Oktovian; Hendra Winarsa; Dijan Mardiati (LPPM Universitas Pamulang, 2020)
This Community Service aims to add insight and develop youth creativity in managing the youth organization at hamlet 11, Pengasinan village, Bogor district which is business-oriented by utilizing assets in the surrounding environment. Besides providing insight to youth the importance of the activities of the control function of all activities related to the economy and business and encourage community leaders to take an active role in supporting the work program of Youth Organization. Community Service Activities carried out from 8 - 10 November 2019 were carried out using mentoring, counseling, practice and training methods to explain comprehensively from the management side of the optimization of financial and business activities. The results of the assistance and counseling in this Community Service activity were management experience and knowledge gained by youth participants of youth organization at hamlet 11, Pengasinan village, Bogor, West Java. That are 1. Optimization of assets for business, 2. Strategic role of the community, 3. Business concepts, 4. Production factors, 5. Business & entrepreneurship, 6. Identification of opportunities and risks. The participants were very enthusiastic and responded intelligently to the discussions. So that with the increasing understanding of Finance and Business, it is expected to be applied in carrying out business activities in the Youth Organization in the environment of hamlet 11, Pengasinan, Bogor, West Java.Keywords: The community services, Youth Organization, Optimization of financial and business